The Importance of Human Emotions for Wildlife Conservation - Castillo-Huitrón, Nathalia M.; Naranjo, Eduardo J.; Santos-Fita, Dídac; Estrada-Lugo, Erin (Frontiers in Psychology, 2020)
Animals have always been important for human life due to the ecological, cultural, and economic functions that they represent. This has allowed building several kinds of relationships that have promoted different emotions in human societies. The objective of this review was to identify the main emotions that humans show toward wildlife species and the impact of such emotions on animal population management. We reviewed academic databases to identify previous studies on this topic worldwide. An analysis of the emotions on wildlife and factors causing them is described in this study. We identified a controversy about these emotions. Large predators such as wolves, coyotes, bears, big felids, and reptiles, such as snakes and geckos, promote mainly anger, fear, and disgust. This is likely due to the perceptions, beliefs, and experiences that societies have historically built around them. However, in some social groups these animals have promoted emotions such as happiness due to their values for people. Likewise, sadness is an emotion expressed for the threatening situations that animals are currently facing. Furthermore, we associated the conservation status of wildlife species identified in the study with human emotions to discuss their relevance for emerging conservation strategies, particularly focused on endangered species promoting ambiguous emotions in different social groups.